Predictors predisposing to orocutaneous fistula occurrence following free flap reconstruction - Wenlu Li; Shuang Wu; Junhui Yuan; Fan Meng; Chunmiao Xu; Hailiang Li (Frontiers in Oncology, 2022)
ObjectivesTo explore the possible risk factors of orocutaneous fistula (OCF) development in free flap reconstruction of the tongue/floor of the mouth (TFOM).MethodsData of patients who underwent free flap reconstruction of the TFOM were retrospectively analyzed. The association between clinicopathologic variables and OCF occurrence was analyzed using univariate and multivariate analyses.ResultsAltogether, 469 patients were enrolled. OCF occurred in 43 patients with a rate of 9.2%. The univariate analysis revealed the negative effects of smoking, preoperative albumin level, cachexia, T4 stage, neck dissection, entire resection of the floor of the mouth (FOM), segmental mandibulectomy, and surgical site infection on OCF occurrence. The multivariate analysis confirmed the independence of cachexia (p<0.001, 4.386[1.883–9.472]), tumor stage (p<0.001, 2.738[1.482–6.629]), entire FOM resection (p<0.001, 6.332[2.110–14.432]), and surgical site infection (p<0.001, 5.376[1.998–11.218]) in affecting the OCF development.ConclusionsOCF development following free flap reconstruction of the TFOM was relatively uncommon, but significantly associated with presence of cachexia, T4 stage, entire FOM resection, and surgical site infection.